1-Methylcyclopropene counteracts ethylene promotion of fruit softening and roles of MiERF2/8 and MiPG in postharvest mangoes - Li, Rui; Ma, Jiheng; Gu, Hui; Jia, Wenjun; Shao, Yuanzhi; Li, Wen (Frontiers in Plant Science, 2022)
Ethylene burst is an important sign of the initiation of postharvest mango ripening and softening is a typical characteristic of fruit ripening. However, the intrinsic link between ethylene release and fruit softening during ripening of postharvest mangoes is still not clear. The aim of this study was to investigate the effects of ethylene and its action inhibitor 1-methylcyclopropene (1-MCP) on fruit softening and ripening and the underlying regulatory mechanisms. Results showed that ethephon (ETH) promoted ethylene release and enhanced MDA content and activities of cell wall degrading enzymes, whereas 1-MCP treatment exhibited an opposite effect. Moreover, qRT-PCR indicated that the transcription levels of genes involved in cell wall degradation (MiPG, Miβ-GAL and MiPE), ethylene biosynthesis (MiACO1 and MiACS6) and signal response factor (MiERF8) were remarkably induced by ETH. Correlation analysis further revealed that the production of ethylene was significantly negatively correlated with firmness, but positively correlated with MDA content, activities of cell wall degrading enzymes and expressions of MiPG and Miβ-GAL. Furthermore, yeast one hybrid (Y1H) assay showed that MiERF2/8 could directly bind to the promotor of MiPG and then regulate its transcription. These findings suggest that ethylene production is closely associated with fruit softening, and MiERF2/8 and MiPG may play crucial roles in regulation of ripening and softening of postharvest mangoes.